Physical activity interventions for cardiopulmonary fitness in obese children and adolescents: a systematic review and meta-analysis - Chaochao Wang; Zuguo Tian; Yuting Hu; Qiaoyou Luo (BMC, 2023)
Abstract Purpose This study [PROSPERO CRD42023416272] systematically analysed the effects of a physical activity intervention on cardiorespiratory fitness in obese children and adolescents and elucidated the factors that influenced those effects. Methods A systematic review of the literature on physical activity interventions for improving cardiopulmonary fitness in obese children and adolescents from January 1, 2011, to March 1, 2023, was conducted. The search was performed on the Web of Science and PubMed databases, and the selected literature was first screened and then assessed for quality. Finally, a systematic review was conducted. Results Out of the initially identified 1424 search records, 28 studies were eventually included in the systematic review. These studies encompassed a total of 2724 participants aged 5 to 18 years, with the publication dates of the literature primarily ranging from 2011 to 2023. Physical activity was found to effectively improve the following parameters in obese children and adolescents: weight [mean difference (MD), -2.03 (95% confidence interval, -2.59 to -1.47), p < 0.00001], maximal oxygen consumption [MD, -1.95 (95% CI, -1.06 to -2.84), p < 0.0001], heart rate [MD, -2.77 (95% CI, -4.88 to -0.67), p = 0.010], systolic blood pressure [MD, -8.11 (95% CI, -11.41 to -4.81), p < 0.00001], and diastolic blood pressure [MD, -4.18 (95% CI, -5.32 to -3.03), p < 0.00001]. High-intensity exercise was found to yield greater improvements than low- to moderate-intensity exercise in maximal oxygen consumption [MD, 1.43 (95% CI, 0.04 to 2.82), p = 0.04] and diastolic blood pressure [MD, -6.94 (95% CI, -10.61 to -3.26), p = 0.0002] in obese children and adolescents. Conclusion Physical activity can effectively improve the body weight, maximal oxygen consumption, heart rate, systolic blood pressure, and diastolic blood pressure of obese children and adolescents. The type of physical activity directly influences the participation interest of obese children and adolescents, with moderate- to high-intensity physical activity showing the most significant impact on intervention outcomes. High-frequency, long-term interventions yield better results than short-term interventions.